The association of exogenous dietary antioxidant micronutrient intake and consumption timing with urinary albumin excretion among U.S. adults - Li, Hangxu; Ge, Jingping; Tong, Wenhui; Chen, Pengpeng; Sun, Pan; Lu, Sujue; Sun, Li; Chen, Yang; Li, Yangyang; Wang, Jun; Li, Jianfei; Mao, Lantian; et al. (Frontiers in Immunology, 2025)
BackgroundOxidative stress plays a central role in the pathogenesis of chronic kidney disease (CKD) and is closely linked to glomerular injury and microvascular endothelial dysfunction. Urinary albumin excretion (UAE) is a sensitive early marker of renal damage and systemic inflammation. Although dietary antioxidants are recognized to modulate oxidative stress, the impact of both their cumulative intake and timing on UAE remains unclear.ObjectivesTo investigate the association between the Composite Dietary Antioxidant Index (CDAI)—including both total daily intake and intake at different meals—and the incidence of elevated UAE among adults in the United States. We also aimed to evaluate whether the timing of antioxidant intake, particularly in the evening, modifies this relationship.MethodsWe analysed data from 23,214 adults aged ≥20 years in the U.S. National Health and Nutrition Examination Survey (NHANES) 2009–2018. CDAI was determined using dietary intakes of six antioxidants (vitamins E, A, C, carotenoids, selenium, and zinc) across breakfast, lunch, and dinner. UAE was defined as a urinary albumin-to-creatinine ratio (ACR) >30 mg/g. Weighted multivariable logistic regression, restricted cubic spline analysis, component-independent effect analysis, and analysis of subgroups were used to evaluate the associations and interactions.ResultsHigher CDAI was greatly connected to reduced odds of UAE (fully adjusted OR per SD increase: 0.98; 95% CI: 0.97–0.99; P = 0.041). Antioxidant intake during dinner showed the strongest inverse association with UAE (P < 0.01), while breakfast and lunch intake were not significantly related. The difference between dinner and breakfast CDAI (ΔCDAI) was also inversely associated with UAE. Subgroup analysis revealed effect modification by BMI: the protective association was attenuated in participants with obesity (BMI ≥ 30).ConclusionsBoth the quantity and timing of dietary antioxidant intake are associated with urinary albumin excretion. Evening antioxidant consumption and a higher ΔCDAI may offer enhanced renal protection, potentially via circadian modulation of oxidative stress and inflammation. These findings support a chrononutrition-based approach to kidney health and warrant further interventional studies.